A generalized additive model analysis of school classroom environment and students' refractive state progression - Meng Qin; Wei-xing Shi; Shan-xi Gao; Yue Niu; Jing-wei Zheng (BMC Public Health)
Abstract Background The study, undertaken in Fengxian District, Shanghai, seeks to investigate the correlation between the sanitary conditions of high school classrooms and the changes in students' uncorrected visual acuity and refractive status, given their predominantly classroom-centric lifestyle and the considerable academic pressures they encounter. Methods Utilizing a cluster random sampling approach, we randomly selected 48 classrooms for monitoring from 8 high schools within the jurisdiction, taking into account factors such as classroom orientation and floor level. A cohort comprising 1087 students was enrolled and followed for a year, with their refractive data being collected. A generalized additive model was employed to examine the associations between classroom environmental factors and students' visual acuity as well as refractive status. Results Significant increases were observed in the spherical equivalent, cylinder, and corneal astigmatism for both the right and left eyes from 2022 to 2023 (P < 0.001). However, no significant change was noted in uncorrected visual acuity (P > 0.05). The compliance rate for blackboard size (height) was 100%, with an average of (1.16 ± 0.06) m and a minimum of 1.06 m. None of the classrooms met the standards for the distance between the multimedia display and the front seat, with an average of (177.26 ± 17.78) m. Classroom per capita area, blackboard size (height), and the distance between the multimedia display and the front seat influenced changes in uncorrected visual acuity. Additionally, classroom per capita area affected changes in the spherical equivalent. The window-to-ground area ratio and blackboard reflectance ratio impacted changes in astigmatism values at 90°-180° (J180) and 45°-135° (J45). Blackboard size (width) and the window-to-ground area ratio influenced changes in students' corneal astigmatism. The classroom with the least impact on refractive status had a per capita area of 1.6 m2, a blackboard size (width) of approximately 4.2 m, and a window-to-floor area ratio of around 0.27. Conclusions Schools should adhere to national standards to enhance the classroom visual environment and further improve the compliance rate.